Heat and Mass Transfer: Fundamentals and Applications - Yunus A. Cengel, Afshin J. Ghajar (India McGraw Hill Education, 2022)
School of Mathematics and Natural Science
MIR No: 178
Order Date: 2024-09-09
Order No: CU/OPEX/LIBRARY/33/2024-25
Received Date: 2024-01-10
Keywords: Technology, Engineering, Chemical engineering